Prevalensi dan Karakteristik Interaksi Obat Potensial pada Resep Pasien Anak Rawat Inap: Evidence dari Rumah Sakit Regional di Indonesia - Rizky Aulia; Cholisoh, Zakky (Jurnal Ilmiah Farmasi, 2026)
Background: Drug interactions represent a significant medication safety concern among pediatric inpatients. Pediatric patients possess distinct pharmacokinetic characteristics compared to adults, rendering them more vulnerable to adverse effects from concurrent drug administration. Objective: This study aimed to analyze potential drug-drug interactions (DDIs) in the prescriptions of pediatric inpatients at Dr. H. Andi Abdurrahman Noor Regional Hospital, Tanah Bumbu Regency. Method: A descriptive cross-sectional study with retrospective data collection was conducted on 143 patients meeting the inclusion criteria from a total of 221 patients during the period of September–November 2025. Drug interaction identification was performed using the drugs.com database. Results: Results showed that of the 143 analyzed prescriptions, 81 (56.6%) contained potential drug interactions, comprising 27 interacting drug pairs and a total of 107 interaction events. By mechanism, pharmacokinetic interactions predominated at 55.1%, followed by pharmacodynamic interactions at 44.9%. By severity, moderate interactions were most prevalent (54.2%), followed by minor (36.4%) and major (9.3%). The most frequently interacting drug pairs were paracetamol–ranitidine (18.7%), cefotaxime–gentamicin (13.1%), and diazepam–valproic acid (8.4%). The most clinically significant major interactions included diazepam–phenobarbital, gentamicin–furosemide, furosemide–propranolol, and dexamethasone–phenobarbital.Conclusion: These findings highlight the high prevalence of potential DDIs in pediatric inpatients and underscore the necessity for rigorous therapeutic monitoring and active clinical pharmacist involvement in the prescribing process.